Additional Medical Support of Antibiotic Therapy: the Need or Polypharmacy? Part 1. Probiotics - L.S. Ovcharenko; A.A. Vertegel (Zaslavsky O.Yu., 2013)
The paper presents an analysis of the results of current researches on the need, effectiveness and safety of additional pharmacological prevention for adverse events associated with the use of antibiotics in children. The authors conclude that because the positions of initial antibacterial agents for use in children in Ukraine are clearly, in a graded sequence defined by national protocols, and the efficacy and safety of probiotic use for the prevention of antibiotic-associated diarrhea in children has not been determined, the only way out of this situation is rational choice of first-line antibiotic.